Applications send and receive SMS with Visual Basic 6.0 - Jonas Panggabean; Robin Antoni Sianipar (Marqcha Institute, 2023)
Communication technology has become an important part of various areas of life. Because of the many conveniences offered, communication technology can hardly be separated from various aspects of human life. With the rapid development of communication technology, it has had a positive impact on society. In addition, communication technology is capable of shortening distances, saving costs, and being able to penetrate space and time. Short Message Service or better known as SMS is now widely used by the public as a communication tool. The advantages of SMS are low cost, fast and direct to the destination. Starting from children, teenagers, adults to the elderly, almost all of them take advantage of this SMS technology. Initially, SMS was only used for interpersonal communication. But now with the times, SMS users are growing. For example, for polling an audition, accessing lecture scores, sending criticism and suggestions to the mass media for publication and many other uses. To be able to do these things, of course, support from adequate software & hardware is needed